Biculturalism and attributional complexity: Cross-cultural leadership effectiveness - Lakshman, C (Journal of International Business Studies, 2013)
Although biculturals represent a growing demographic, the nascent literature on biculturals has not addressed their cross-cultural leadership capabilities or effectiveness. Attributional patterns and variations across cultures are crucial, and call for higher attributional complexity (AC) and attributional knowledge to reduce cultural distance. This study provides a systematic theoretical connection between biculturals and their higher levels of AC and attributional knowledge, which account for their cross-cultural competence. This connection is then linked to attributional processes, drawing from recent literature on attributional models of leadership. The proposed theoretical model posits that biculturals have higher levels of AC and attributional knowledge, which helps them make more accurate attributions, which are also less culturally biased. Managerial behaviors resulting from these attributions lead to cross-cultural leadership effectiveness, because they absorb uncertainty on the part of subordinates. The proposed model addresses both cognitive and emotional competency elements of cross-cultural leadership. We contribute to the international business literature by providing a theoretical model for examining factors critical to the cross-cultural leadership effectiveness of leaders who have more than one cultural profile. Managerial implications for selection and training of international executives are discussed in the context of culture-specific and culture-general capabilities. Contributions, limitations, and boundary conditions are also discussed.